(untitled) (Medical Forum Monthly, 2024)
Objective: To determine expression of BCL-2 protein in Adenoid cystic carcinoma of salivary glands. Study Design: Descriptive study. Place and Duration of Study: This study was conducted at the Departments of Surgery, Lahore General Hospital, Mayo Hospital, and de’Montmorency college of Dentistry, Lahore from February 2017 to August 2017. Materials and Methods: Thirty five cases of Adenoid cystic carcinoma (ADCC), of salivary glands were selected. Slides were prepared by routine hematoxylin and eosin (H & E) staining, as well as by Immunohistochemistry (IHC) for BCL-2. Grading of ADCC was done as low, intermediate and high grades on H&E sections. Scoring of BCL-2 expression was determined on BCL-2 immunohistochemical stained slides. Data was entered into SPSS version 21 and descriptive statistics were determined. Results: In this study most common age group affected was 41-60 years age (40%), cases of ADCC were more common in female as compared to male (54%) Expression of BCL-2 was strongly positive in all cases of ADCC. In major salivary gland parotid glands was the most common site while in minor salivary glands most common site was palate. Majority cases reported as excisional biopsy (54.3%) with size 2-5cm (68.8%). Histopathologically 19 cases (54%) were categorized as high grade tumor. All cases showed expression of BCL-2 irrespective of the grade of the tumor. Conclusion: BCL-2 protein is expressed in Adenoid cystic carcinoma. Its expression is helpful in grading small biopsies, predicting behavior, and planning target therapy of Adenoid cystic carcinoma